La vulgarisation de la notion d’adolescence dans l’Europe de l’après-Seconde Guerre mondiale : échanges et circulations du savoir « psy » entre l’espace francophone européen et l’Italie - Laura Di Spurio (Amnis)
This paper discusses the emergence of the notion of adolescence throughout post-Second World War Europe. Jointly examining the French and Italian bodies of knowledge in this field from 1945 up to 1958, this comparative analysis allows for one to have a sense of the evolutionary process that lead to psychology becoming the expert discipline in the field of adolescence. Based on the intense editorial production characterising this period, this paper analyses the various debates revolving around the construction of a specific knowledge on adolescence, especially around the vulgarisation of this new field of study. Furthermore, the comparative perspective of this paper allows one to observe the flow of knowledge between these two areas as well as to understand the prominent role of Catholicism in the making and spreading of these new fields of knowledge.